Knowledge, attitude, and practice towards COVID-19 among Syrian people resident in Turkey - Ali Jadoo, Saad Ahmed; Dastan, Ilker; Al-Samarrai, Mustafa Ali Mustafa; Yaseen, Shukur Mahmood; Abbasi, Asiyeh; Alkhdar, Hassan; Al Saad, Mohammed; Danfour, Omar Mohamed (Journal of Ideas in Health, 2020)
Background: Measuring knowledge, attitude, and practice towards COVID-19 helps policymakers observe knowledge gaps and provide key messages to people to act better against the pandemic. This study aims to assess the knowledge, attitude, and practice towards COVID-19 among Syrian people resident in Turkey. Methods: A cross-sectional study designed to assess the knowledge, attitude, and practice towards COVID-19 among the Syrian people resident in Turkey. The data were collected via a web-based and self-administered questionnaire of 313 participants from 17-31 July 2020. SPSS version 16.0 was recruited to analyze the data using univariate and multivariable regression data analyses. Results: Our finding as the first study among Syrian people resident in Turkey found a high rate of good knowledge, attitude, and practice towards COVID-19 accordingly with 83.0%, 72.0%, 84.0%. Regression analysis showed that age-group of 45 years and more years, marital status of being married, female gender, living in urban area were significantly associated with upper knowledge score. Age-group of 45 years and more significantly associated with positive attitude score but inversely being married and unemployed statues significantly associated with a negative attitude. Regarding practice score, married and female people had better practice, but poor-rated health status was significantly associated with the weak practice. Conclusion: Although our finding showed a good rate for knowledge, attitude, and practice towards COVID-19, but it needs to improve cause of many barriers on Syrian people resident in Turkey, such as living in a crowded place, distant from health care services, losing whole or part of their income due to COVID-19 as an economic crisis, different language barriers. Some groups like men, people living in a rural area, and those unemployed or lost their job should be exposed by timely and accurate knowledge.